Phylogeography of the rabies virus isolated from canids in the North and Northeast of Brazil - Carnieli Jr, P.; Oliveira, R. N.; Castilho, J. G.; Vieira, L. F. P. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Antigenic variant 2 of the Rabies Virus (RABV), typically found in dogs in Brazil, still circulates in the North and Northeast of Brazil in spite of mass vaccination campaigns against rabies in domestic animals. Previous studies have shown that this variant is made up of two main genetic lineages: one found in dogs (Canis familiaris) and another typically found in wild canids, particularly the crab-eating fox (Cerdocyon thous), which is known in Brazil as cachorro do mato. C. thous is currently the only wild land species in which RABV is continually isolated, with an average of 20 cases/year. Although previous studies and phylogenetic analyses of the N and G genes and intergenic G-L region all confirmed the existence of these two genetic lineages, the way in which the lineages had dispersed temporally and spatially remained to be elucidated. We sequenced a 1388 nucleotide-long region of the RABV N gene from 53 typical canid samples. The phylogeography of the dataset obtained was determined using the BEAST (Bayesian Evolutionary Analysis Sampling Trees) program with the following data for the script: Evolutionary Model K3Puf+G4; Partitioning into codon positions (1+2)+3; Molecular clock relaxed uncorrelated lognormal; Demographic model coalescent exponential growth; Dispersion model relaxed randon walking (RRW). The results can be summarized as follows. The common ancestor of the RABV in the samples analyzed became established around 1900 in the border region between the states of Paraíba and Pernambuco.